Laryngomalacia and failure to thrive - A case report - Rita Barroca Macedo; Maria Sousa Dias; Luís Salazar; Pedro Alexandre; Catarina Viveiros; Marco Pereira; Jorge Spratley (Hygeia Press di Corridori Marinella, 2024)
Introduction: Laryngomalacia (LGM) is the most common congenital anomaly of the larynx and the most frequent cause of stridor in the newborn. Even though it can be a source of concern and anxiety to parents, a large majority of cases usually resolve spontaneously within 18 months of life. However, in infants with signs of severity, a multidisciplinary approach and surgical intervention might be necessary. Case report: We report the case of a full-term 7-week-old infant girl, previously hospitalized in the Neonatal Intensive Care Unit and diagnosed with type II LGM (Olney's classification). She presented to the Paediatric Emergency Department with stridor at rest, vigorous chest wall retractions and poor weight gain (increase of 10 g/day, weight under the 3rd percentile). The infant was admitted to monitor respiratory symptoms and investigate her failure to thrive. However, irrespective of feeding modifications, and after exclusion of other causes of failure to thrive, the infant maintained an insufficient weight gain. Additionally, respiratory symptoms remained exuberant and surgical intervention was determined as the optimal treatment. At 3 months old, supraglottoplasty was performed. At 18 months, she has a weight in the 3rd-15th percentile range (WHO curves) and is clinically asymptomatic. Conclusion: LGM is a remarkably frequent cause of stridor in infants, but only a rare number of cases require other interventions beyond symptomatic measures. In this report, surgical intervention was of paramount importance to ensure normal growth, emphasising the impact of a multidisciplinary approach in such cases.